Memory and cultural landscape at the Khami World Heritage site, Zimbabwe - Sinamai, Ashton, author.
1 online resource.
Keywords: "This book focuses on a forgotten place--the Khami World Heritage site in Zimbabwe. It examines how professionally-ascribed values and conservation priorities affect the cultural landscape when there is a disjuncture between local community and national interests. It also explores the epistemic violence that often accompanied colonial heritage management and archaeology in southern Africa. The central premise is that the history of the modern Zimbabwe nation, in terms of what is officially remembered and celebrated, inevitably determines how that past is managed. The book is about how places are experienced and remembered through narratives and how the loss of this heritage memory may mark the un-inheriting of place. It is informed by the author's experience of living near, and later, working at Great Zimbabwe and Khami as an archaeologist. Great Zimbabwe is a resource for the state's contentious narrative of unity, and a tool for cultural activism among communities whose cultural rights are denied through the nationalisation and globalisation heritage. At Khami, there is only silence as it has lost its historical gravity. To understand how Khami has been un-inherited, I use archives and traditional narratives to build a biography for Khami which I then use to build the lost cultural landscape at Khami"--